Potential of Oil Mixture of Palm Oil and Mineral as Future Transformer Oil - Pungut Ibrahim; Naidhila Junaidi; Ahmad Razani Haron; Megat Muhammad Ikhsan Megat Hasnan; Nur Aqilah Mohamad; Herwansyah Lago; Chai Chang Yii (International Journal of Integrated Engineering, 2024)
This study investigates the electrical performance of oil mixtures that composed of palm oil and mineral oil for potential use as an alternative transformer insulating fluid. The breakdown voltage of eleven oil samples, prepared with varying ratios of palm oil and mineral oil, is measured at temperatures of 50 °C, 60 °C, and 70 °C. The results show that the breakdown voltage generally decreases as the percentage of palm oil decreases and the percentage of mineral oil increases. However, beyond certain points, the breakdown voltage starts to increase again. For example, at 50 °C, the mixture with 60 % palm oil and 40 % mineral oil exhibited the lowest breakdown voltage, while the mixture with 100 % mineral oil had the highest breakdown voltage. At 60 °C, the sample with 40 % palm oil and 60 % mineral oil had the highest breakdown voltage, and at 70 °C, the sample with 40 % palm oil and 60 % mineral oil again exhibited the highest breakdown voltage. The study also utilized Arrhenius plots to investigate the thermal activation energy of the oil mixtures, which provides insights into their thermal stability. The results demonstrate the potential of palm oil as a cost-effective and environmentally friendly option for transformer insulation, offering valuable implications for sustainable transformer technology development. Further investigation into moisture content in the oil mixtures and its correlation with thermal activation energy is recommended for future work.